The Effect of Health Education Using Banners on Stunting Prevention in Children (2–5 Years Old) - Lani, Maria Ferderika; Milka Langmau; Maria Leoanak (Poltekkes Kemenkes Kupang, 2024)
Stunting is a chronic nutritional problem that remains a global health issue requiring serious attention, including in Indonesia. This condition affects children’s physical growth, brain development, and future productivity. This study aims to determine the effect of health education using banner media on increasing mothers’ knowledge in efforts to prevent stunting among children aged 2–5 years at Sikumana Health Center, Kupang City. This research used a quantitative method with a quasi-experimental design, employing a one group pre-test post-test approach. The study was conducted from March to April 2024 with a total of 64 mothers who had stunted children aged 2–5 years, selected through a purposive sampling technique. Data were collected using a questionnaire consisting of 15 closed-ended questions and analyzed using the Wilcoxon statistical test. The results showed a significant increase in mothers’ knowledge after receiving health education through banner media, with an Asymp. Sig. (2-tailed) value of 0.000 (< 0.05). This indicates that health education with banner media has a significant effect on improving mothers’ knowledge in stunting prevention. In conclusion, health education through banner media is effective in increasing maternal understanding and awareness about stunting prevention. It is recommended that health centers utilize visual educational media such as banners to enhance public health knowledge and help reduce stunting prevalence.